Evaluación de los conocimientos, actitudes y prácticas que tienen los estudiantes sobre el diagnóstico, manejo y tratamiento de trauma dento-alveolar. (2023)
By means of the present research, the aim was to know the level of competencies of the students of the Antonio Nariño University School of Dentistry, Armenia campus, on dentoalveolar traumas. For which it was decided to conduct a descriptive qualitative research, in which a semi-structured interview was conducted and reviewed by the two endodontists to establish that the questions were clear and concise, an informed consent was structured in which the participants of the research accepted to be part of it, thus applying it to six students who will be chosen from the fifth semester by means of a non-random sampling. When the interviews were obtained, the answers were analyzed after being transcribed, units of meaning were made and, in addition to that, cross-coding was also done, where the answers were divided according to the category to which they correspond, compared and it was observed what they have in common, in order to evaluate the knowledge and fulfill the objectives of this work.